An X-ray microtomographic study of natural white-spot enamel lesions - Cochrane, N J; Anderson, P; Davis, G R; Adams, G G; Stacey, M A; Reynolds, E C (Journal of dental research, 2012)
White-spot enamel lesions are an early presentation of dental caries and are ideally managed by non-invasive procedures. The aim of this study was to characterize white-spot enamel lesions by x-ray microtomography. In particular, mineral content across the lesion from the surface to the base of the lesion was measured and surface layers defined. Molars with long buccal white-spot enamel lesions were collected, photographed, and each sectioned to produce 3 500-µm-thick sections. The sections were mounted and imaged by quantitative x-ray microtomography at a 15-µm voxel size. We analyzed line profiles through the middle of each 3D image to determine mineral content and depth. The surface layer thickness of the lesions ranged from 35 to 130 µm, with the maximum mineral content in this layer being 74% to 100% of that of sound enamel. The average mineral content across the lesions ranged from 1.73 to 2.48 g/cm(3). No significant differences could be found between lesions clinically categorized as active and those categorized as inactive. However, for depth-matched active and inactive lesions, the active lesions exhibited a more porous surface layer than the inactive lesions. White-spot enamel lesions are highly variable, with surface layers of considerable thickness.